ChemInform Abstract: Metal‐Centered Zintl Ions Isolated by Direct Extraction from Endohedral Intermetallic Precursor: [Co1‐x@Sn9]4‐ (x ≈ 0.32) and [Co2@Sn17]5‐. Issue 3 (January 2015) - He, Haiyan; Klein, Wilhelm; Jantke, Laura‐Alice; Faessler, Thomas F.
Abstract Single crystals of the new compounds K[K([2.2.2]crypt)]3[Co0.68@Sn9] (I) and [K([2.2.2]crypt)]5 [Co2@Sn17]·en·Tol (II) are prepared from solutions of K4.79Co0.79Sn9, and Kryptofix 222 in en and layered with toluene.